Cultura política y partidos autonómicos españoles en Twitter - Said-Hung, Elías Manuel; Mottareale, Daria; Sánchez-Esparza, Marta (Revista Mexicana de Sociologia, 2024)
Este trabajo busca establecer el tipo de cultura política y el tipo de estrategia comunicativa promovida por los grupos políticos autonómicos en España en Twitter. Se realiza un análisis de tópicos a partir de 18 610 tuits, publicados entre septiembre de 2019 y febrero de 2020, por parte de usuarios asociados a los partidos, líderes y portavoces en el Congreso de los Diputados de 11 grupos políticos españoles. Los datos muestran rasgos asociados a la estructura de los mensajes y temas abordados, así como estrategias de comunicación y culturas políticas diferenciadas según el perfil político.
Political culture and Spanish autonomists parties on Twitter
This work seeks to establish the type of political culture and communication strategy that autonomist political groups in Spain promote on Twitter. It presents the results of a topic analysis of 18 610 tweets published between September 2019 and February 2020 by users associated with eleven Spanish political groups, their leaders, and spokespersons in the Congress of Deputies. The data show features associated with the structure of the messages and topics addressed, as well as communication strategies and differentiated political cultures that vary according to the political profile of the groups.
Keywords: cultura política; estrategias de comunicación; redes sociales; política; actores políticos; Twitter; political culture; communication strategies; social networks; politics; political actors; Scopus